The effect of Plant Growth Promoting Rhizobacteria (PGPR) on the growth of rice: a review / Nur Safura Hanim Ishak - Ishak, Nur Safura Hanim (Faculty of Plantation and Agrotechnology, 2017)
This review mainly focused on identifying the effectiveness of PGPR on the growth and yield of rice. PGPR is a bacterial that act as a biofertilizer that help the rice plant in nutrient uptake from soil or rhizophere through the bacterial. PGPR is 100% natural and are an organic material which is environmental friendly. The used of PGPR as biofertilizer on rice are not only decrease the usage of chemical in rice cultivation but also can prevent soil pollution happen from excessive usage of chemical fertilizer (Gupta et al, 2015). The effectiveness of PGPR on the growth of rice was studied using parameter such as the number of tiller, number of grain panicle, length of root and plant height. While the yield of rice measured on the grain and straw yield. Besides, these researchers found that the results of using PGPR are successful between the comparison of uninoculated and inoculated of rice plant through the experiments conducted. Hence, it can be concluded that application of PGPR has immense potential to be as agricultural crop inoculants as they promote plant growth as well as improve the yield.